Road to Paris-2024: The path of Brazilian volleyball athletes goes through the youth national teams - Dell'Antonio, E.; Machado, J. M.; Mendes, F. G.; Gonçalves, G. H. T. (Journal of Human Kinetics, 2025)
This study analyzed the transition of Brazilian volleyball athletes from youth national teams to adult national teams, and examined the relative age effect in the selection of athletes for youth categories and their transition to the adult category. In youth categories, 326 athletes participating in the U18 and U20 women's and U19 and U21 men's world championships between 2001 and 2021 were prospectively analyzed. In the adult category, a retrospective analysis was conducted on 55 athletes who participated in the Olympic Games or World Championships between 2004 and 2022. Our results showed that approximately 20% of athletes participating in youth categories advanced to the adult national team. However, around 80% of adult teams comprised athletes who were part of youth categories. An athlete who progressed through both youth categories was 35 times more likely to be selected to the adult national teams compared to an athlete who only participated in the U18/U19 youth team. In youth national teams, there was a higher call-up rate for athletes born earlier. Despite this, athletes born later were more likely to advance to the adult national team.